Programmed cell death pathways in hearing loss: A review of apoptosis, autophagy and programmed necrosis - Wu, Junhao (Cell Prolif, 2020)
Programmed cell death (PCD)—apoptosis, autophagy and programmed necrosis—is any pathological form of cell death mediated by intracellular processes. Ototoxic drugs, ageing and noise exposure are some common pathogenic factors of sensorineural hearing loss (SNHL) that can induce the programmed death of auditory hair cells through different pathways, and eventually lead to the loss of hair cells. Furthermore, several mutations in apoptotic genes including DFNA5, DFNA51 and DFNB74 have been suggested to be responsible for the new functional classes of monogenic hearing loss (HL). Therefore, in this review, we elucidate the role of these three forms of PCD in different types of HL and discuss their guiding significance for HL treatment. We believe that further studies of PCD pathways are necessary to understand the pathogenesis of HL and guide scientists and clinicians to identify new drug targets for HL treatment.